PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KESULITAN PESERTA DIDIK MEMBACA AL-QUR’AN DI SMP NEGERI 3 TANIWEL KECAMATAN TANIWEL BARAT KABUPATEN SERAM BAGIAN BARAT - Rini Assel (IAIN Ambon, 2022)
Abstract: The purpose of this study was to determine the role of Islamic religious education teachers in overcoming the difficulties of students reading the Qur'an at SMP Negeri 3 Taniwel, West Taniwel District, West Seram Regency. The type of research is descriptive qualitative research. The results of the study indicate that the role of Islamic religious education teachers in overcoming the difficulties of students reading the Koran at SMP Negeri 3 Taniwel includes; a. The teacher as a teacher, the role of the teacher as a coach, the teacher as an example. Factors supporting the implementation of the duties or roles of Islamic religious education teachers are facilities and infrastructure (learning media), teacher awareness in carrying out responsibilities and student learning motivation. Inhibiting factors are the lack of time allocation and lack of parental attention. Keywords: Islamic Religious Education, Difficulty Reading The Qur'an. Abstrak: Tujuan penelitian ini untuk mengetahui peranan guru pendidikan agama Islam dalam mengatasi kesulitan peserta didik membaca al-Qur’an di SMP Negeri 3 Taniwel Kecamatan Taniwel Barat Kabupaten Seram Bagian Barat. Tipe penelitian adalah penelitian deskriptif kualitatif. Hasil penelitian menunjukkan bahwa peranan guru pendidikan agama Islam dalam mengatasi kesulitan peserta didik membaca al-Qur’an SMP Negeri 3 Taniwel meliputi; a. Guru sebagai pengajar, Peran guru sebagai pelatih, Guru sebagai teladan. Faktor pendukung pelaksanaan tugas atau peranan guru pendidikan agama islam adalah Sarana dan prasarana (media pembelajaran), Kesadaran guru dalam melaksanakan tanggung jawab dan Motivasi belajar peserta didik. Faktor penghambat yakni Kurangnya alokasi waktu dan Kurangnya perhatian orang tua.